Penyajian Laporan Keuangan dan Pernyataan Standar Akuntansi Keuangan (PSAK) Syariah 112 Pada Lembaga Badan Wakaf Cabang Medan - Tri Bagus Pertiwi; Rahmat Daim Harahap; Dita Sri Utami; Khairina Anisa Zaisa; Wardoni Hikman Ritonga (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Financial statements are the most important part of an institution, which is called financial statements. In an effort to support the presentation of relevant sharia-based financial statements, a guideline for financial statement preparers must be made, the guideline is the Statement of Financial Accounting Standards (PSAK). PSAK 112 aims to regulate the presentation and disclosure of Waqf Accounting or the presentation of financial statements in waqf institutions. The management of waqf institutions is a very vital part, because in managing waqf a person or related institution must really understand the issue of waqf by looking at sharia financial statements. This type of research is a type of qualitative research. Secondary data is also used by researchers obtained through journals, articles and other media. The results of the study indicate that the presentation of financial statements prepared by the Al-Quran Waqf Board of Medan Branch with PSAK 112 on